Carolina Israelite : how Harry Golden made us care about Jews, the South, and civil rights - Hartnett, Kimberly Marlowe (University of North Carolina Press, 2015)
"This first comprehensive biography of Jewish American writer and humorist Harry Golden (1902-1981), author of the 1958 national best-seller 'Only in America', illuminates a remarkable life intertwined with the rise of the civil rights movement, Jewish popular culture, and the sometimes precarious position of Jews in the South and across America during the 1950s"--